Utilization of Fruit Extracts for Sunscreen - Satya Wydya Yenny; Fauzana Nazifah (Indonesian Journal of Global Health Research, 2025)
ABSTRACT Indonesia is one of the countries with high exposure to sunlight, and most of its population works outdoors, making skin protection necessary. While sunlight provides benefits, it also has harmful effects on the skin if exposed excessively. Ultraviolet rays, UVB and UVA, work synergistically to damage the skin, thus requiring prevention or protection to reduce the negative impacts of radiation. Excessive sun exposure is the main exogenous mediator of skin damage. The negative effects of sun exposure on the skin lead to various skin problems such as darkening, wrinkles, dullness, and the appearance of dark brown spots, and it can even cause skin cancer. Therefore, using sunscreen is crucial as it can prevent UV rays from penetrating the skin. This study uses a literature review design, where relevant scientific articles are analyzed to explore the potential of natural ingredients as sunscreen agents. A total of 9 articles were collected from various databases, including PubMed, ScienceDirect, and Google Scholar, using specific keywords related to UV protection, natural sunscreen, and bioactive compounds in plants. The selection of articles was based on inclusion and exclusion criteria, ensuring that only recent and relevant studies were considered. Natural ingredients have not yet been widely utilized in the sunscreen industry. Plants contain substances that can be extracted and serve as a potential source of sunscreen due to their photoprotective properties. This provides insight into the ability of plants to protect the skin through the compounds they contain, such as bioactive compounds like phenolic substances and antioxidants.